Isolasi, Identifikasi Serta Uji Aktivitas Antibakteri Senyawa Golongan Triterpenoid Dari Ekstrak Daun Binahong (Anredera cordifolia (Ten.) Steen) Terhadap Staphylococcus aureus dan Escherichia coli - Murdianto, Agus Ria (Chem Info Journal, 2013)
Isolation, identification, and antibacterial activity examination of triterpenoid compounds from leaves of Binahong (Anredera cordifolia (Ten.) Steen). Maseration of 1 kg dry powder of those leaves using n-hexane respectively yielded 43,2 g. The n-hexane extracts obtained contained triterpenoids based on fitochemical test of Lieberman-Burchard. Compound separation of the n-hexane extract using column chromatography produced isolate which contained triterpenoids in fraction A. The isolate inhibited the growth of Staphylococcus aureus and Escherichia coli at Minimal Inhibition Concentration 100 ppm with weak inhibition zone. The results of identification using UV-Vis spectrophotometry showed a maximum absorption at a wavelength of 239 nm. Based on FT-IR spectrogram shows the groups, there were OH , C=C, C-C, C=O, -C-H, -CH3,-CH2, and C-O. LC-MS spectrogram indicated that the isolated had a molecular weight 562 g / mol of suspected compounds 2,3,19,23-tetrahydroxy-12-ene-24,28-dimethyl ester.